Torment - Kate, Lauren (New York : Delacorte Press, 2010)
In a desperate effort to save Luce from the Outcasts-immortals who want her dead, Luce and Daniel are forced to be apart from each other and, as she discovers more about her past lives, Luce starts to suspect that Daniel may have lied to her about their shared past and that she may have been destined to be with someone else all along.
Sequel to : Fallen.
Keywords: Paranormal fiction; Love -- Fiction; Reincarnation -- Juvenile fiction; Angels -- Juvenile fiction